UNITE ME - 623748 Mafi, Tahereh (New York : HARPER, An Imprint of HarperCollinsPublishers, 2014)
"Juliette will not stand alone. In a battle that will decide the fate of her world. In Destroy me, Warner, the ruthless leader of Sector 45, refuses to let her go. In Fracture me, Adam, Juliette's first love, will do anything to get her back."--Page 4 of cover.